Pengaruh Penerapan Manajemen Mutu Terhadap Kualitas Sumberdaya Pendidik TPQ Darussalam Blokagung Tegalsari Banyuwangi Tahun Pelajaran 2017 - Ach. Aminullah (IAI Darussalam, 2017)
This research aims to: (1) the effect of the application of quality management TPQ Darussalam Blokagung Blokagung Tegalsari Banyuwangi,(2) Mengeahui quality educator resources Darussalam TPQ Blokagung Blokagung Tegalsari Banyuwangi, (3) the effect application quality management to quality educator resources Darussalam TPQ Blokagung Tegalsari Banyuwangi. In this study using a quantitative descriptive method by using product moment on the validity of test data and to search for data reliability using alpha formula, whereas in the hypothesis testing using the F test and t-test then for the data analysis techniques using normality test using regression models. The study population was the guardian of students TPQ Darussalam totaled 250. To measure the variables, the researchers used questionnaires to variations in methods of teaching and learning motivation. After analyzing the data collected, it was found that (1) the application of quality management TPQ Darussalam Blokagung Tegalsari good Banyuwangi. (2) the quality of educator resources Darussalam TPQ Blokagung Tegalasari excellent Banyuwangi. (3) No effect on the Quality of Implementation Quality Management Resource Educator TPQ Darussalam Blokagung Tegalsari Banyuwangi in the school year 2017 was 36.3%.